Coupled nitrate N and O stable isotope fractionation by a natural marine plankton consortium - Rohde, Melissa M.; Granger, Julie; Sigman, Daniel M.; Lehmann, Moritz F. (Frontiers in Marine Science, 2015)
The stable nitrogen (N) and oxygen (O) isotope ratios (15N/14N and 18O/16O, respectively) of nitrate (NO3-) were measured during incubations of freshly collected seawater to investigate the effect of light intensity on the isotope fractionation associated with nitrate assimilation and possible co-occurring regeneration and nitrification by in situ plankton communities. Surface seawater was collected off the coast of Vancouver, Canada, in late fall and in late summer and was incubated under different laboratory light conditions for 10 and 30 days, respectively. In the late summer experiments, parallel incubations were supplemented with 15NH4+ and H218O tracers to monitor co-occurring nitrification. Differences in irradiance in the fall incubations resulted in reduced nitrate consumption at low light, but had no distinguishable impact on the N-isotope isotope effect (15ε) associated with NO3- assimilation, which ranged between 5 and 8‰. The late-summer community incubations, in contrast, showed reduced growth rates at low light and more elevated 15ε of 11.9 ± 0.4‰, compared to 8.4 ± 0.3‰ at high-light conditions. The seasonal differences could reflect physiological adaptations of the fall plankton community to reduced irradiance, such that their incubation at low light did not elicit the increase in proportional cellular nitrate efflux required to raise the isotope effect. In both the fall and summer incubations, the ratio of the coincident rises in the δ15N and δ18O of NO3- was comparable to previous monoculture phytoplankton experiments, with a ∆δ18O:∆δ15N of ~1, regardless of light level. A decoupling of ∆δ18O:∆δ15N is expected if nitrification occurs concomitantly with nitrate assimilation. The lack of such decoupling is best explained by the absence of significant nitrification in any of our study’s treatments, an interpretation supported by our inability to identify any tracer 15N and 18O uptake into the NO3- pool in the late-summer community incubations.